Shank3 Exons 14–16 Deletion in Glutamatergic Neurons Leads to Social and Repetitive Behavioral Deficits Associated With Increased Cortical Layer 2/3 Neuronal Excitability - Yoo, Taesun; Cho, Heejin; Park, Haram; Lee, Jiseok; Kim, Eunjoon (Frontiers in Cellular Neuroscience, 2019)
Shank3, an abundant excitatory postsynaptic scaffolding protein, has been associated with multiple brain disorders, including autism spectrum disorders and Phelan-McDermid syndrome. However, how cell type-specific Shank3 deletion affects disease-related neuronal and brain functions remains largely unclear. Here we investigated the impacts of Shank3 deletion (exons 14–16) in glutamatergic neurons with a dorsal telencephalic origin on synaptic and behavioral phenotypes in mice. Neuronal excitability was abnormally increased in layer 2/3 pyramidal neurons in the medial prefrontal cortex in mice with a glutamatergic Shank3 deletion, similar to results obtained in mice with a global Shank3 deletion. In addition, excitatory synaptic transmission was abnormally increased in layer 2/3 neurons in mice with a global, but not a glutamatergic, Shank3 deletion, suggesting that Shank3 in glutamatergic neurons are important for the increased neuronal excitability, but not for the increased excitatory synaptic transmission. Neither excitatory nor inhibitory synaptic transmission was altered in the dorsal striatum of Shank3-deficient glutamatergic neurons, a finding that contrasts with the decreased excitatory synaptic transmission in global and Shank3-deficient GABAergic neurons. Behaviorally, glutamatergic Shank3-deficient mice displayed abnormally increased direct social interaction and repetitive self-grooming, similar to global and GABAergic Shank3-deficient mice. These results suggest that glutamatergic and GABAergic Shank3 deletions lead to distinct synaptic and neuronal changes in cortical layer 2/3 and dorsal striatal neurons, but cause similar social and repetitive behavioral abnormalities.